Description of two new species of Anagyrini (Hymenoptera: Encyrtidae), with some records from India. (2nd October 2017) - Bin Zeya, Shahid; Majid Jamali, Mohd; Fatima, Farha
Abstract: Two new species of Anagyrini (Encyrtidae: Tetracneminae), Anagyrus deccanus Zeya & Jamali, sp. nov. and Cryptanusia bela Zeya & Fatima, sp. nov., are described. The following species are newly recorded from the Indian States: Anagyrus aquilonaris (Noyes & Hayat) (Odisha, Maharashtra), A. levis Noyes & Hayat (Andhra Pradesh), Apoleptomastix rufipleuris Kerrich (Uttarakhand), A. rufiscapus Kerrich (Himachal Pradesh), Dusmetia fuscipennis (Noyes & Hayat) (Odisha), Leptomastix tsukumiensis Tachikawa (Himachal Pradesh), and Rhopus beatus Hayat & Khan (Uttarakhand). http://www.zoobank.org/urn:lsid:zoobank.org:pub:D6303180-25ED-4344-8CF4-CE509B3ECDEF